Risk factors and management of hyperuricemia after renal transplantation - Zi, Xiaoyu; Zhang, Xi; Hao, Chuan; Wang, Zhenxing (Frontiers in Surgery, 2023)
Hyperuricemia (HUA) is a common complication after renal transplantation. Currently, there is no uniform consensus on factors which increase the risk for and treatment of HUA in renal transplant recipients. The purpose of this review is to summarize current and proposed risk factors and strategies to manage HUA after renal transplantation in order to assist renal function protection and prolong graft survival time.